An optical gamma-ray burst catalogue with measured redshift: I. data release of 535 gamma-ray bursts and colour evolution - Dainotti, Maria; De Simone, B.; Mohideen Malik, R. F.; Pasumarti, V.; Levine, D.; Saha, Navonil; Gendre, B.; Kido, D.; Watson, A. M.; Becerra, R. L.; Belkin, S.; Desai, S.; et al. (Monthly notices of the Royal Astronomical Society, 2024)
We present the largest optical photometry compilation of gamma-ray bursts (GRBs) with redshifts (z). We include 64813 observations of 535 events (including upper limits) from 28 February 1997 to 18 August 2023. We also present a user-friendly web tool grbLC which allows users to visualize photometry, coordinates, redshift, host galaxy extinction, and spectral indices for each event in our database. Furthermore, we have added a Gamma-ray Coordinate Network (GCN) scraper that can be used to collect data by gathering magnitudes from the GCNs. The web tool also includes a package for uniformly investigating colour evolution. We compute the optical spectral indices for 138 GRBs, for which we have at least four ﬁlters at the same epoch in our sample, and craft a procedure to distinguish between GRBs with and without colour evolution. By providing a uniform format and repository for the optical catalogue, this web-based archive is the ﬁrst step towards unifying several community efforts to gather the photometric information for all GRBs with known redshifts. This catalogue will enable population studies by providing light curves (LCs) with better coverage since we have gathered data from different ground-based locations. Consequently, these LCs can be used to train future LC reconstructions for an extended inference of the redshift. The data gathering also allows us to ﬁll some of the orbital gaps from Swift in crucial points of the LCs, e.g. at the end of the plateau emission or where a jet break is identiﬁed.